HUBUNGAN ASUPAN LEMAK, ASUPAN VITAMIN C, DAN STATUS GIZI DENGAN TINGKAT KEBUGARAN JASMANI PADA ATLET CABANG OLAHRAGA PERMAINAN DI SMA RAGUNAN JAKARTA - Siti Ghina Annisa (2021)
Physical fitness is used as a determinant of an individual's health and can be improved through regular physical activity or exercise. According to PPOP DKI Jakarta in 2020, in adolescent athletes of sports games has a physical fitness level of 47% less, 32% moderate, and 21% good. This can happen because it is influenced by several factors such as nutrient intake, socioeconomic status, nutritional status, genetics, and smoking habits. The purpose is to analyze the relationship of fat intake, vitamin C intake, and nutritional status with physical fitness levels in athletes of sports games at SMA Ragunan Jakarta. This research method is cross-sectional design with the number of respondents was 40 athletes who were selected using stratified random sampling and came from the sports of the game at SMA Ragunan Jakarta. Data was taken using primary data and secondary data. Data analysis used is Chi Square Test. The results showed that there is a relationship between fat intake (p = 0.000) and nutritional status (p = 0.037) with physical fitness levels in sports athletes at SMA Ragunan Jakarta. In addition, there is no relationship between vitamin C intake (p = 0.230) and physical fitness levels in athletes in sports games at SMA Ragunan Jakarta. It is expected that athletes pay more attention to the food consumed while not in the dormitory and the SMA Ragunan Jakarta (PPOP DKI Jakarta) can provide education and counseling to athletes and parents related to food arrangements and daily food intake.